(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
"For several decades, artificial intelligence (AI) has played an integral role in healthcare, progressively transforming clinical diagnostics and treatment methodologies. In the realm of dentistry, AI presents a groundbreaking opportunity to enhance diagnostic precision, optimize treatment strategies, and alleviate the burden on clinicians. Among the most pressing concerns in dental health, periodontal disease and cariology stand out as critical areas where AI-driven innovations can significantly contribute to early intervention and management. Periodontal disease, a progressive condition affecting the periodontium—including gingival tissues and alveolar bone—is a predominant factor in adult tooth loss. Simultaneously, cariology, which encompasses the etiology, diagnosis, and treatment of dental caries, represents another domain where AI algorithms exhibit substantial potential. Leveraging sophisticated computational models, AI systems can process and interpret dental imaging data with remarkable accuracy, enabling the early identification of pathological changes that might otherwise evade detection in conventional examinations. This review traces the historical trajectory of AI integration in healthcare before delineating its transformative role in contemporary dentistry. Additionally, it examines the fundamental architectures of AI frameworks, including artificial neural networks (ANNs), convolutional neural networks (CNNs), and ensemble methods such as random forest algorithms, emphasizing their respective contributions to diagnostic advancements. Furthermore, this article critically evaluates AI’s expanding influence across various dental subspecialties, encompassing periodontology, cariology, endodontics, prosthodontics, and orthodontics. From automating disease classification and quantifying alveolar bone deterioration to refining image-based diagnostics, AI introduces unprecedented analytical capabilities into dental practice. However, despite its transformative potential, the widespread adoption of AI in dentistry remains constrained by a range of technical, ethical, and infrastructural challenges that necessitate comprehensive resolution for seamless clinical integration.”